Toxicity of azo-dyes combined with TiO2 nanoparticles - Kroath, M.; Punz, E.; Joubert, I.A.; Himly, M.; Geppert, M. (Open Schools Journal for Open Science, 2020)
Azo-dyes are organices compounds frequesntly used for food colring for example in sweets. A characteristic feature of az-=dyes is the axo-group (-N=N) as part of the chromophore. In parallel, nanoparticles (NPs) are more and more used as food additives and this, the encoubter of NPs with azo-dyes is highly likely. In particular, TiO2 NPs are inciroporated into foods under the tearm E171.